Revealing a new region of gamma-ray emission in the vicinity of HESS J1825–137. Issue 1 (17th February 2019) - Araya, M; Mitchell, A M W; Parsons, R D
Abstract: HESS J1825–137 is a bright very high-energy gamma-ray source that has been firmly established as a pulsar wind nebula (PWN), and one of the most extended gamma-ray objects within this category. The progenitor supernova remnant (SNR) for this PWN has not been firmly established. We carried out an analysis of gamma-ray observations in the region of HESS J1825–137 with the Fermi –LAT that reveals emission in the direction away from the Galactic plane.  The region lies beyond the PWN and reaches a distance from the pulsar compatible with the supposed location of the SNR shock front. The spectrum of the gamma-rays is hard with a photon index of ∼1.9 in the 10–250 GeV range. Several scenarios for the origin of the emission are discussed, including the SNR as a source of high-energy particles and the 'leakage' of leptons from the PWN.